Baicalein Induces Apoptosis of Rheumatoid Arthritis Synovial Fibroblasts through Inactivation of the PI3K/Akt/mTOR Pathway. (7th September 2022) - Zhang, Xue; Guan, Xia; Piao, Yingshi; Che, Xiangguo; Si, Mengge; Jin, Jingchun
Abstract : Purpose . Rheumatoid arthritis (RA) shows abnormal proliferation, apoptosis, and invasion in fibroblast-like synoviocytes (FLSs). Baicalein (BAI), extracted from Scutellaria baicalensis, is used as an anticancer drug through inducing cancer cells apoptosis. However, the mechanism of BAI in RA progression still remains unknown. Here, we demonstrated that BAI inhibited FLS proliferation and migration, whereas it enhanced apoptosis via the PI3K/Akt/mTOR pathway in vitro . Methods . Cell viability and colony formation were analyzed by MTT and plate colony formation assays in SW982 cells, respectively. Apoptosis was detected by flow cytometry and western blotting. Epithelial-mesenchymal transition (EMT), MMP family proteins (MMP2/9), and the PI3K/Akt/mTOR pathway were detected by western blot. Cell migration was detected by scratch healing assay under BAI treatment in SW982 cells. Results . BAI dose-dependently inhibited cell viability and colony forming in SW982 cells. BAI upregulated apoptotic proteins and downregulated EMT-related proteins, resulting in enhanced cell apoptosis and inhibited cell migration in SW982 cells. BAI also dose-dependently inhibited the phosphorylation of PI3K, Akt, and mTOR. Conclusions . These results indicated that BAI inhibited FLSs proliferation and EMT, whereas induced cell apoptosis through blocking the PI3K/Akt/mTOR pathway, supporting clinical application for RA progression.